Introduction - Pereira da Silva, Luciano; Meneguette Junior, Messias [UNESP]; Marchi, Carlos Henrique (My University, 2023)
In this chapter we comment on the general ideas of our book. In it we highlight the objectives we have in mind when preparing each of its chapters. We present the problems that we are going to solve as well as a flowchart with all the steps from discretization of the domain to numerical solutions.